Sistema para programação remota de velocidade de moto-bomba de pivô central acionada por inversor de frequência - Loureiro, Gláucio Ferreira (2017)
Energy consumption must be taken into consideration when regarding irrigation. The use of a Variable Frequency Drive (VFD) significantly reduces energy consumption during irrigation, by adjusting the rotation of the motor axis to the need of the hydraulic system. Seasonality alters water levels in the reservoir, affecting water pressure. In many occasions, it is impossible to go to field for the necessary adjustments to the frequency inverter. In this context, the objective was to develop a system capable of remotely controlling the VFD, using a Raspberry pi and an Arduino, associated to a potentiometer. The system was validated from the frequency data of seven central pivots, later comparing the values inserted into the system and those provided by the frequency inverter. The t Student statistical test was used with a significance level of 5%, for comparative ends. The system can contribute with changes to the frequency values at a distance. The frequency values inserted into the system presented no significant difference when compared to those provided by the VFD. Energy consumption can be estimated by using efficiency equations for the VFD or pump, affecting global efficiency and active electric power. In some cases, it is difficult to determine the efficiency of the variable frequency drive, demanding the use of estimation equations. In this sense, a comparison study between the equations proposed by Bernier & Bourreout (1999), Wallbom-Carlson (1998) and Sarbu & Borza (1998) was developed to verify the existence of differences between the efficiencies proposed by these authors and the impact of said differences over the calculations of the active electric power. For comparative effect, a variance analysis was developed using the Snedecor F test at a significance level of 5%. There was no significant difference in the low rotations for the equations proposed by Bernier & Bourreout (1999) and Wallbom-Carlson (1998). The calculation of global efficiency used for the Bernier & Bourreout (1999) efficiency equation presented values lower to those of the remaining equations, due to the use of a higher number of parameters.